Dielectric constant reduction using porous substrates in finline millimetre and submillimetre detectors - North, C; Audley, MD; Glowacka, D; Goldie, D; Grimes, P; Johnson, B; Maffei, B; Melhuish, S; Piccirillo, L; Pisano, G; Tsaneva, V; Withington, S; et al. (2008)
Finlines are planar structures which allow broadband and low loss transition from waveguide to planar circuits. Their planar structure and large substrate makes them ideal for integration with other planar circuits and components, allowing the development of an on chip Polarimeter. We have developed a method of extending the employment of finlines to thick substrates with high dielectric constants by drilling or etching small holes into the substrate, lowering the effective dielectric constant. We present the results of scale model measurements at 15GHz and cryogenic measurements at 90GHz which illustrate the excellent performance of finline transitions with porous substrates and the suitability of this technique for extending the bandwidth of finline transitions.